Grandparents Raising Grandchildren: Guiding Your Grandchild’s Behavior - Part 2 - Millie Ferrer; Angela Falcone (EDIS, 2002)
This document is FCS 2187-Eng, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2002. Its goal is to provide grandparents with information for guiding children’s behavior.